The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.1007/s00520-020-05767-5
|View full text |Cite
|
Sign up to set email alerts
|

Palliative care provision at a tertiary cancer center during a global pandemic

Abstract: COVID-19 was first reported in Wuhan, China, in December 2019; it rapidly spread around the world and was declared a global pandemic by the World Health Organization in March 2020. The palliative care program at the Princess Margaret Cancer Centre, Toronto, Canada, provides comprehensive care to patients with advanced cancer and their families, through services including an acute palliative care unit, an inpatient consultation service, and an ambulatory palliative care clinic. In the face of a global pandemic,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
21
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
10

Relationship

5
5

Authors

Journals

citations
Cited by 21 publications
(24 citation statements)
references
References 23 publications
1
21
0
2
Order By: Relevance
“…Several groups have shared their experiences with establishing a telemedicine-based palliative care program [ 28 , 37 39 , 40 ▪▪ , 41 , 42 ]. Chavarri-Guerra et al [ 40 ▪▪ ] describe the feasibility of providing supportive and palliative care using telemedicine to patients with advanced cancer in Mexico, despite low availability of resources and patients with significant symptom burden.…”
Section: Widespread Adoption Of Telemedicinementioning
confidence: 99%
“…Several groups have shared their experiences with establishing a telemedicine-based palliative care program [ 28 , 37 39 , 40 ▪▪ , 41 , 42 ]. Chavarri-Guerra et al [ 40 ▪▪ ] describe the feasibility of providing supportive and palliative care using telemedicine to patients with advanced cancer in Mexico, despite low availability of resources and patients with significant symptom burden.…”
Section: Widespread Adoption Of Telemedicinementioning
confidence: 99%
“…This review identified a knowledge gap about how palliative care interventions for people who use substances should be provided in communicable disease outbreaks other than HIV. Though the knowledge identified in our scoping review is generally applicable to other life-limiting illnesses and communicable disease outbreaks, novel models of care (eg, virtual care) are likely required to deliver high-quality, equitable palliative care for people who use substances that prevents and minimises risk of transmission of infectious diseases other than HIV 49 50…”
Section: Discussionmentioning
confidence: 99%
“…Palliative care educational endeavors should prioritize the development and dissemination of resources for non-specialist palliative care teams around communication skills. 31 …”
Section: Discussionmentioning
confidence: 99%